Clove Essential Oil (Syzygium aromaticum L. Myrtaceae): Extraction, Chemical Composition, Food Applications, and Essential Bioactivity for Human Health - José Nabor Haro-González (MDPI AG, 2021)
Clove (Syzygium aromaticum L. Myrtaceae) is an aromatic plant widely cultivated in tropical and subtropical countries, rich in volatile compounds and antioxidants such as eugenol, β-caryophyllene, and α-humulene. Clove essential oil has received considerable interest due to its wide application in the perfume, cosmetic, health, medical, flavoring, and food industries. Clove essential oil has biological activity relevant to human health, including antimicrobial, antioxidant, and insecticidal activity. The impacts of the extraction method (hydrodistillation, steam distillation, ultrasound-assisted extraction, microwave-assisted extraction, cold pressing, and supercritical fluid extraction) on the concentration of the main volatile compounds in clove essential oil and organic clove extracts are shown. Eugenol is the major compound, accounting for at least 50%. The remaining 10–40% consists of eugenyl acetate, β-caryophyllene, and α-humulene. The main biological activities reported are summarized. Furthermore, the main applications in clove essential oil in the food industry are presented. This review presents new biological applications beneficial for human health, such as anti-inflammatory, analgesic, anesthetic, antinociceptive, and anticancer activity. This review aims to describe the effects of different methods of extracting clove essential oil on its chemical composition and food applications and the biological activities of interest to human health.